Response of soil nitrogen retention to the interactive effects of soil texture, hydrology, and organic matter. Issue 1 (21st March 2013) - Castellano, Michael J.; Lewis, David Bruce; Kaye, Jason P.
Abstract: [1] Advances in nitrogen (N) saturation and retention theories have focused on soil organic matter (SOM) biogeochemistry in the absence of dynamic soil hydrology. Here we exploit two soil types with contrasting textures that span a hillslope gradient to test hypotheses that suggest N saturation symptoms are regulated by the interactive effects of soil texture, OM, and hydrology on N retention capacity (maximum pool size) and N retention kinetics (N retention rate). Down the hillslope gradient, soil solution nitrate (NO3 ) concentrations sampled with lysimeters increased, while 15 NO3 ‐N retention decreased. Landscape location (upland, hillslope, and toeslope) and soil type interacted to affect soil solution NO3 concentrations so that the downslope increase in NO3 was greater in sandy versus silty soils. These patterns manifest despite a downslope increase in soil organic carbon (SOC) and C/N ratios. A positive correlation between saturated hydraulic conductivity and soil solution NO3 sampled in zero‐tension lysimeters during precipitation events suggested that high hydraulic conductivity promotes periodic rapid NO3 transport at rates that exceed retention kinetics. The downslope increase in soil solution NO3 in spite of a concomitant increase in SOC and C/N ratios provides an important contrast with previous N saturation research that highlights negative correlations between SOM C/N ratios and NO3 concentrations and suggests NO3 transport along connected hillslope flow paths may overwhelm stoichiometric sinks for inorganic N retention in SOM. Our results reveal important gaps in N retention theory based on SOM biogeochemistry alone and demonstrate how coupled biogeochemical and hydrological models can improve predictions of N saturation, particularly when considering periodic advective NO3 transport in the vadose zone. We show that in coarse‐textured soils, low capacity for protection of SOM N by association with fine mineral particles interacts with rapid hydrological flushing of NO3 to enhance the expression of ecosystem N saturation symptoms. Key Points: Soil particle size affects SOM N stabilization Soil particle size affects soil hydrology Hydrology and OM stabilization affect N retention kinetics and capacity